EFEK MUSIK TERHADAP PRESTASI ANAK USIA PRASEKOLAH: STUDI KOMPARASI EFEK LAGU ANAK, DOLANAN JAWA, DAN MUSIK KLASIK - Budi Raharja (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractThis study aimed to investigate effects of Indonesian childrens songs, Javanesechildrens songs, and Western classical music as the musical backgrounds for thelearning environments in the kindergartens on the students achievement. Thestudy was conducted in the area of Sinduadi with a population comprising 45students of TK ABA Kutu Asem, 35 students of TK Pertiwi Sinduadi, and 55students of TK Tunas Muda Kutu Dukuh. The students were asked to listen to thetree types of songs, each for one month and were then given a test. To investigatethe effect of each treatment, the pretest and posttest data were employed. Thepretest was administered as a control before the treatment was given and theposttest to find out the effect of the treatment. The tests were administered tomeasure the students thinking ability and skills and the questionnaire to collect thedata on the students environmental characteristics. The students achievementscores, the time to finish the pretest and posttest, and their characteristics wereanalyzed by (a) the paired-samples t-test at p .05 using SSPS 12.0 for Windows tofind out the effect of the treatment, and (b) the description of the studentscharacteristics to interpret the meanings. The results of the study showed thatIndonesian childrens songs and Javanese childrens songs had positive effects andWestern classical music had negative effects. This showed that there was acorrelation among the students musical environment, the musical treatment effect,and the students achievement. The treatment with music that the students werefamiliar with had positive effects or made them learn with comfort so that theywere able to improve their achievement, but that with music that they wereunfamiliar with made them unable to concentrate so that their achievement wentdown.Keywords: music, concentration, students achievement